Investing in Islamic fixed deposit accounts: a technology acceptance model perspective - Hanudin, Amin; Ramayah, T; Suhartanto, Dwi; Muhammad, Ali; Abdul Razak, Dzuljastri; Mohd Zulkifli, Muhammad (International Journal of Business and Society, 2022)
This study is aimed at explaining the factors determining consumer acceptance of online Islamic fixed deposit accounts. Besides, the mediating role of attitude is also examined. Considering the Technology Acceptance Model (TAM), this study evaluates the impacts of perceived usefulness, perceived ease of use along with attitude on consumer acceptance using a survey questionnaire. In terms of findings, PLS results suggest that perceived usefulness, perceived ease of use and attitude are instrumental in determining consumer acceptance. Attitude also serves as a valid mediator for the model developed. Likewise, the topic of this study is focused on consumer acceptance instead of actual behaviour along with its limited number of factors examined. The results obtained provide a benchmark to managers of Islamic banks to promote online transactions among bank customers on Islamic fixed accounts. Besides, this study expands the TAM’s application to include online Islamic fixed deposit accounts.